Solvent-mediated molar conductivity of protic ionic liquids - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Physical Chemistry Chemical Physics, 2015)
The molar conductivity, A(m), of protic ionic liquids (PILs) in molecular solvents is measured at 298.15 K. The decrease in the A(m) values of PILs is observed with an increase in the concentration of PILs. The limiting molar conductivities, A(m)(0), were obtained for each PIL in different molecular solvents using a least squares method. The A(m)(0) data for PILs were correlated with the structural aspects of PILs and solvent properties. The polar protic solvents show poor ionic association as compared to the polar aprotic solvents, which is discussed on the basis of the hydrogen bond donating (HBD) ability of solvents and PILs. The alkyl chain substitution of anions plays a significant role in the ionic association of the PILs. The diffusion coefficient D-0 and the transport number t were determined, which were consistent with the A(m)(0) values of PILs in water. The A(m)(0) and D-0 values are dependent on the hydrodynamic radius of anions of these ionic liquids. The extent of ionic association for each PIL was discussed using temperature dependent A(m) data for aqueous PIL systems in terms of the Walden plot.

Comparative investigation of the ionicity of aprotic and protic ionic liquids in molecular solvents by using conductometry and NMR spectroscopy - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Chemphyschem, 2016)
Electrical conductivity (sigma), viscosity (), and self-diffusion coefficient (D) measurements of binary mixtures of aprotic and protic imidazolium-based ionic liquids with water, dimethyl sulfoxide, and ethylene glycol were measured from 293.15 to 323.15K. The temperature dependence study reveals typical Arrhenius behavior. The ionicities of aprotic ionic liquids were observed to be higher than those of protic ionic liquids in these solvents. The aprotic ionic liquid, 1-butyl-3-methylimidazolium tetrafluoroborate, [bmIm][BF4], displays 100% ionicity in both water and ethylene glycol. The protic ionic liquids in both water and ethylene glycol are classed as good ionic candidates, whereas in DMSO they are classed as having a poor ionic nature. The solvation dynamics of the ionic species of the ionic liquids are illustrated on the basis of the (HNMR)-H-1 chemical shifts of the ionic liquids. The self-diffusion coefficients D of the cation and anion of [HmIm][CH3COO] in D2O and in [D-6]DMSO are determined by using H-1 nuclei with pulsed field gradient spin-echo NMR spectroscopy.
Keywords: conducting materials; Electrochemistry; electrostatic interactions; Ion pairs; ionic liquids

Plasmonic behavior of ionic liquid stabilized gold nanoparticles in molecular solvents - Thawarkar, Sachin; Thombare, Balu; Khupse, Nageshwar D. (New Journal of Chemistry, 2017)
In this paper, we have demonstrated the facile synthesis of stable gold nanoparticles (AuNPs) using imidazolium ionic liquids (ImILs) as a stabilizer as well as a surfactant and their surface plasmon resonance (SPR) in different molecular solvents with varying dielectric properties. The preparation of AuNPs capped with N,N'-dialkyl ImILs of different chain lengths (denoted as [C-4, C-n-im]Br, n = carbon number of the alkyl chain) has been investigated. With one long alkyl chain (n >= 14), these AuNPs could be stably dispersed in solution over a month. The amphiphilic nature of the imidazolium salt dictates the stability and dispersion of these AuNPs in organic or aqueous solvents. Alkyl chain lengths (n >= 14) and the amount of ImILs have insignificant effect on the size of AuNPs and they possess an average size of 5 nm. These ionic liquid stabilized AuNPs were exploited to examine their optical properties when exposed to various solvent systems by measuring the change in the SPR spectrum. It was seen that the position of the SPR band of AuNPs is greatly influenced by the solvents under consideration. The shift in the SPR absorption band is observed to be in the range of 520 nm to 605 nm for AuNP@[C-4,C-16-im]Br from nonpolar to highly polar solvents. The considerable discovery presented here is that the lambda(SPR) of the SPR shifts to the blue with the increase of carbon atom in the alcohol chain from methanol to 1-decanol. Also for polyethylene glycols (PEGs), the lambda(SPR) shifts to the blue with the increase in molecular weight from PEG 200 to PEG 600. In above both cases, the variation in SPR of AuNPs is observed according to the dielectric properties of the medium in addition to the steric factor of alcohols and PEGs during their interaction with AuNP surfaces.

Ionic liquid-responsive phase transfer of gold nanoparticles: anionic metathesis - Thawarkar, Sachin; Nirmale, Trupti C; More, Sahebrao; Ambekar, Jalindar D; Kale, Bharat B; Khupse, Nageshwar D (Langmuir, 2019)
In this work, a fresh approach has been proposed for the efficient transfer of gold nanoparticles (AuNPs) from an aqueous to organic phase by the metathesis reaction or anion exchange reaction. Here, we synthesized ionic liquid 1-butyl 3-hexadecyl imidazolium bromide [C(4)C1(6I)m]-Br-stabilized AuNPs which exhibit excellent stability in solution. Transfer of Au@[C(4)C(16)Im]Br from an aqueous to organic phase was investigated by the metathesis reaction with different hydrophobic ionic liquid-forming salts such as LiNTf2, LiClO4, and KPF6. The anionic exchange process in ionic liquids at the AuNP surface to make hydrophilic to hydrophobic AuNPs is demonstrated. It was found that hydrophobic ionic liquids provide the most effective transfer of AuNPs from the aqueous to organic phase. Interestingly, we have noticed no change in color, size, and shape of AuNPs for more than a month, indicating more efficient transfer of AuNPs in organic solvents, which remained stable for over a month. The ionic liquids with anions NTf2-, ClO4-, and PF6- make the AuNP surface hydrophobic, indicating their good dispersibility in nonpolar solvents. Finally, these AuNPs exhibit excellent sensitivity toward the refractive index of organic solvents, which is correlated with the surface plasmon resonance (SPR) lambda(SPR) bands.

Binary mixtures of aprotic and protic ionic liquids demonstrate synergistic polarity effect: an unusual observation - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2020)
In this communication, we demonstrate the solute-solvent and solvent-solvent interactions in the binary mixtures of two aprotic ionic liquids, namely 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, with the protic ionic liquid 1-methylimidazolium acetate. The synergistic effects as expressed by the solvatochromic parameter are noted. This observation is in contrast to the mixing of protic ionic liquids 1-methylpyrrolidium acetate and 4-methylmorpholine acetate with 1-methylimidazolium acetate, respectively. It appears that the synergistic effects in the binary mixtures of aprotic and protic ionic liquids are caused by the formation of hydrogen bonds, since cations are dominant H-bond donors while anions are dominant H-bond acceptors. Preferential solvation models are used to describe the solute-solvent interactions in the binary ionic liquid mixtures.
Keywords: binary mixture; Ionic liquid; polarity; Preferential solvation; synergetic effect

Lead-free solid state mechanochemical synthesis of Cs2NaBi1-XFeXCl6 double perovskite: reduces band gap and enhances optical properties - Udavant, Rohini; Thawarkar, Sachin; Rondiya, Sachin; Shelke, Ankita; Aher, Rahul; Ajithkumar, Thalasseril G.; Cross, Russell W.; Dzade, Nelson Y.; Jadkar, Sandesh (Inorganic Chemistry, 2023)
Efficient and stable lead-free halide double perovskites (DPs) have attracted great attention for the future generation of electronic devices. Herein, we have developed a doping approach to incorporate Fe3+ ions into the Cs2NaBiCl6 crystal unit and reveal a crystallographic and optoelectronic study of the Cs2NaBi1-xFexCl6 double perovskite. We report a simple solid-state mechanochemical method that has a solvent-free, one-step, green chemistry approach for the synthesis of Cs2NaBi1-xFexCl6 phosphor. The analysis of powder X-ray diffraction (XRD) data determines the contraction of the lattice due to the incorporation of Fe3+ cations, and this effect is well supported by X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), Raman spectroscopy, and solid-state nuclear magnetic resonance spectroscopy (ss-NMR). The band gap is reduced with increasing Fe content owing to the strong overlap of the Fe-3d orbitals with Cl-3p orbitals and shift of the valence band maxima (VBM) toward higher energies, as confirmed by ultraviolet photoelectron spectroscopy (UPS) and density functional theory (DFT) analyses. Photoluminescence (PL) studies of Cs2NaBi1-xFexCl6 phosphors exhibit a large Stokes shift, broadband emission, and increased PL intensity more than ten times for 15% of Fe content phosphor with enhancement in the average decay lifetimes (up to 38 ns) compared to pristine Cs2NaBiCl6 DP. These results indicate that the transition of dark self-trapping of excitons (STEs) into bright STEs enhances yellow emission. XRD, UV, and thermo-gravimetric analysis (TGA) confirmed that the Cs2NaB1-xFexCl6 DPs have good structural and thermal stabilities. Our findings indicate that the doping of Fe3+ cations into the Cs2NaBiCl6 lattice is a constructive strategy to enhance significantly the optoelectronic properties of these phosphors.